2011
DOI: 10.1007/s10530-011-0152-2
|View full text |Cite
|
Sign up to set email alerts
|

Modes of reproduction in three invasive milkweeds are consistent with Baker’s Rule

Abstract: According to Baker's Rule, uniparental reproduction is associated with colonizing plants because it provides a means for population establishment following single long-distance dispersal events. There is, however, limited evidence for the applicability of Baker's Rule to invasive plants. We determined the breeding systems of three invasive milkweed speciesAsclepias curassavica, Gomphocarpus fruticosus and G. physocarpus-in their invaded range in south-east Queensland, Australia. Although dependent on pollinato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 82 publications
1
33
0
Order By: Relevance
“…This prediction has been supported by an important body of evidence (see Crawford, Anderson & Bernardello 2011 for review). Similar observations were made during the colonization process of invasive species outside of their native range (Ward, Johnson & Zalucki 2012; but see Colautti, White & Barrett 2012), in agreement with Baker's (1955) observation that 'the vast majority of weeds are self-compatible or possess strong powers of vegetative reproduction'.…”
Section: Introductionsupporting
confidence: 81%
“…This prediction has been supported by an important body of evidence (see Crawford, Anderson & Bernardello 2011 for review). Similar observations were made during the colonization process of invasive species outside of their native range (Ward, Johnson & Zalucki 2012; but see Colautti, White & Barrett 2012), in agreement with Baker's (1955) observation that 'the vast majority of weeds are self-compatible or possess strong powers of vegetative reproduction'.…”
Section: Introductionsupporting
confidence: 81%
“…; Pyšek et al . ; Ward, Johnson & Zalucki ). Although there is evidence for Baker's Law as a rule, it does not mean that self‐incompatible species cannot become invasive.…”
Section: Discussionmentioning
confidence: 99%
“…; Pyšek et al . ; Ward, Johnson & Zalucki ). For example, in a literature survey comprising 26 naturalized alien species (most of which were invasive), c. 70% of alien plants were autofertile (Burns et al .…”
Section: Introductionmentioning
confidence: 99%
“…This needs to be considered when assessing the demographical advantages of selfing for an invader. Unfortunately, there are very few investigations on this subject for alien species (but see Rodger et al 2010Rodger et al , 2013Ward et al 2012;Mullarkey et al 2013). Studies of plants in the native range have shown that selfing ability and inbreeding depression vary among life forms.…”
Section: Incidence Of Self-pollination In Invasive Alien Florasmentioning
confidence: 99%